RANCANGAN BENTUK PELAPORAN KEUANGAN PEMERINTAH DESA DENGAN PENDEKATAN PERATURAN PEMERINTAH NOMOR 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAHAN - B51111170, Jurnal Dwi Agus Ujianto (Jurnal KIAFE, 2013)
accountability and financial transparancy is necessary in achieving goodgovernance. Not only the central government and local governments but also the villagegovernment. Up to now there is no government regulation requiring the village toprepare financial statements. Sample in this study is Sungai Raya Dalam villagegovernment. The data used in this study is a proof of the village government financialtransactions. The data were analyzed with government accounting standards (SAP).Results from this study is the village government financial reporting in accordance withgovernment accounting standards.Keywords: government, financial, village